A snapshot of novel psychoactive substances (legal highs) use in London. (November 2017) - Norman, Claire; Lee, Geraldine A.
Highlights: There has been an increase in the use of 'legal highs' including synthetic cannabinoids and cathinones. Symptoms of legal high ingestion include seizures, unconsciousness, shortness of breath, vomiting, aggression, paranoia, palpitations, agitation and foaming at the mouth. In terms of emergency care, users were three times more likely to end up seeking emergency medical treatment with NPS than traditional drugs. A retrospective study identified 34 cases and of these, fourteen cases had confirmed NPS use, with clinical presentations including respiratory arrest (n = 1), actively fitting (n = 5) and unresponsive (n = 4).